2016
DOI: 10.1108/jmp-09-2013-0289
|View full text |Cite
|
Sign up to set email alerts
|

A cross-cultural examination of preferences for work attributes

Abstract: Purpose: We examine the relationship between individual-and country-level values and preferences for job/organizational attributes.Design/methodology: Survey data were collected from 475 full-time employees (average of 9 years work experience, and 3 years in a managerial position) enrolled in part-time MBA programs in seven countries. Findings:Preference for a harmonious workplace is positively related to horizontal collectivism, whereas preference for remuneration/advancement is positively related to vertical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…It could be conjectured, for instance, that notions of meaningfulness may vary across cultural or religious communities, and studies could explore this proposition. Only one study by Woodard et al (2016) has attempted to consider cross-cultural differences in meaningful work using notions of collectivism versus individualism. However, as the authors themselves pointed out, their findings were limited by insufficient sample sizes to draw reliable conclusions.…”
Section: Implications For Hrd Theorymentioning
confidence: 99%
“…It could be conjectured, for instance, that notions of meaningfulness may vary across cultural or religious communities, and studies could explore this proposition. Only one study by Woodard et al (2016) has attempted to consider cross-cultural differences in meaningful work using notions of collectivism versus individualism. However, as the authors themselves pointed out, their findings were limited by insufficient sample sizes to draw reliable conclusions.…”
Section: Implications For Hrd Theorymentioning
confidence: 99%
“…Members of collectivist cultures are more likely to derive satisfaction from a job well done(Hofstede and Bond, 1984). Previous studies have divided collectivism into two dimensions: HC and VC (Triandis and Suh, 2002; Woodard et al , 2016; Wong et al , 2018). In HC, people see themselves as similar to others and emphasize on common goals.…”
Section: Theory Background and Hypothesesmentioning
confidence: 99%
“…In VC, people value the integrity of groups, are willing to sacrifice their personal interests for the good of their groups, and support competitions between their teams and other groups. In this dimension, people are willing to submit to authority (Triandis and Gelfand, 1998; Woodard et al , 2016).…”
Section: Theory Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, due to their interdependent self-construal, those with a collectivist orientation are expected to be more sensitive to social approval of their organizations than are those with an individualist orientation. To support this view, research has found that collectivist job seekers attached more importance to the prestige and reputation of an organization than did individualists (Caligiuri et al, 2010;Woodard et al, 2016) and collectivists placed more weight on prestige as a work value (Hartung et al, 2010). Therefore, it is expected that H5a: The positive relationship between collectivist self-concept orientation and VE needs will be stronger than the positive relationship between individualist self-concept orientation and VE needs.…”
Section: Self-enhancement Needs (Social Adjustment and Value Expressimentioning
confidence: 99%